Perfection of primary children’s selection for sport gymnastic training in Kurdistan - Abdulvahid, Dlshad Nihad (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to find ways of perfection of primary children’s selection for sport gymnastic training in Kurdistan. Material: questioning of specialized physical culture HEEs’ students in Ukraine and Kurdistan (n=120, n=120). Physical condition and physical qualities of 7 years’ age boys of Ukraine and Kurdistan (n=56, n=52) were assessed. Results: only 10 Kurdistan students had opportunity to start specialized sport trainings by recommendations of professional coach. Ineffective influence of mass media in involvement of youth in sport trainings was noted. Physical condition level of children corresponds to standards. In most of motor tests Ukrainian children showed better results that their peers from Kurdistan. Conclusions: in Ukraine 42% of children join sports practicing owing to parents’ wish. In Kurdistan 25% of children join sports practicing by recommendations of physical culture teachers. The next by importance factor is example of peers (21% and 33%). In nine from twelve motor tests Kurdistan children yield to their Ukrainian peers. In 20 meters’ run and in shuttle run results of Kurdistan children are better. Confident distinctions were found in quantity of chin ups in lying position.